2021
DOI: 10.5539/jas.v13n2p23
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of Cage Effect and Prebiotic Production Potential of a β-Mannanase, with SBM as Substrate Using Microscopy and Wet Chemistry

Abstract: In vitro assays were carried out to investigate the solubilization of cell walls and generation of mannan oligosaccharides of a b-mannanase-containing commercial product on SBM. Using commercial dosages of the b-mannanase (500 g per ton of feed) cell wall degradation of mannan in SBM cell walls was visualized and an increase in reducing ends (0.12±0.02 mg/mL) and the generation of mannan oligosaccharides of degree of polymerization 2 and 4 (22.9±3.2 mg/L and 398.8±25.4 mg/L) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…It is typically stored outside of the plasmalemma, both in the primary and secondary cell walls, providing a structural as well as an energy storage function 45 . The activity of ß-mannanase at the hemicellulose of the primary cell wall and at the hull of the soybean seed was reported in previous studies 12 , 15 , 46 and is corroborated by our study with a stronger activity at the hull where galactomannans are more concentrated than in other fractions of soybean seeds 47 . It is speculated that pure mannans partially substitute cellulose in the cell wall and might instead provide the hardness and strength to the cell wall structure in soybean endosperm 9 , 48 , 49 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is typically stored outside of the plasmalemma, both in the primary and secondary cell walls, providing a structural as well as an energy storage function 45 . The activity of ß-mannanase at the hemicellulose of the primary cell wall and at the hull of the soybean seed was reported in previous studies 12 , 15 , 46 and is corroborated by our study with a stronger activity at the hull where galactomannans are more concentrated than in other fractions of soybean seeds 47 . It is speculated that pure mannans partially substitute cellulose in the cell wall and might instead provide the hardness and strength to the cell wall structure in soybean endosperm 9 , 48 , 49 .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the degradation of ß-mannans could reduce the stimulation of the innate immune response, leading to higher animal performance 10 , which was demonstrated for ß-mannanase-supplemented corn-SBM based diets 11 . The last effect, termed anti-caging effect, relates to the boosted release of trapped or bound nutrients by the degradation of mannan-associated hemicelluloses in the cell wall 12 , 13 . Sundu et al reported that ß-mannanase supplementation to mannan-rich corn-SBM-copra meal-based diets significantly improved protein and lipid digestibility in poultry 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementation of β-mannanase has been associated with reducing the negative impacts of β-mannans, which are anti-nutritional factors that can bind to nutrients and reduce its digestibility, leading to reduced growth performance in pigs [10]. It has been also known that β-mannanase breaks down these complex polysaccharides having cage effects, which physically interfere with the mode of action of endogenous or microbial enzymes to hydrolyze the nutrients inside the cell wall [21,22]. This study also shows that supplementation of β-mannanase could improve ME in barley, palm kernel meal, sorghum, and soybean meal as well as protein digestibility in copra meal and palm kernel meal.…”
Section: Discussionmentioning
confidence: 99%
“…The poor performance is attributed to the high intestinal viscosity induced by GG, that reduces the passage rate, increases the satiety, reduces the feed intake (also observed in this study), and also impairs the nutrient absorption ( Maisonnier et al, 2003 ; Owusu-Asiedu et al, 2006 ). According to previous studies the positive effects of dietary β-mannanase supplementation on broiler performance is a consequence of a higher ileal digestibility of carbohydrates and amino acids ( Caldas et al, 2018 ; Gomez-Osorio et al, 2021 ; Latham et al, 2018 ; White et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%